The machine learning landscape of top taggers - Kasieczka, Gregor; Plehn, Tilman; Butter, Anja; Cranmer, Kyle; Debnath, Dipsikha; Dillon, Barry M.; Fairbairn, Malcolm; Faroughy, Darius A.; Fedorko, Wojtek; Gay, Christophe; Gouskos, Loukas; F. Kamenik, Jernej; et al. (SciPost physics, 2019)
SciPost Journals Publication Detail SciPost Phys. 7, 014 (2019) The Machine Learning landscape of top taggers
Gesehen am 09.11.2022